Synergistic effects of elastic band and vibration training on muscle strength, balance, and mobility in older women with a history of falls: a randomised controlled trial - Zhang, Zhou; Xiong, Weizhi; Liu, Heng (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study aimed to investigate the effects of combined elastic band resistance training (EBRT) and whole-body vibration training (WBVT) on lower limb isokinetic muscle strength, balance and physical performance in older women with history of falls.MethodsA total of 102 older women with a history of falls was randomly assigned to the elastic band group (n = 28), vibration group (n = 28), elastic band plus vibration group (n = 28) and control group (n = 28) for a 12-week program. All groups performed identical exercises (half squats, static squats, left/right lunges) thrice weekly. The control group trained on a flat ground without elastic bands or vibration; the elastic band group used elastic bands on the flat ground, while the vibration and combined groups exercised on a vibration platform. Training parameters included 3 sets × 10 repetitions with 20-s rest intervals.ResultsPost-intervention, knee flexion peak torque increased by 9.7% (p < 0.05). Total length (TL), elliptical area (EA), total offset index (TAI), timed up and go test (TUG) and five times sit-to-stand test (FTSST) decreased by 16.2%, 14.2%, 21.9%, 16.9% and 14.0%, respectively; and modified fall efficacy scale (MFES) increased by 17.6% (p < 0.01) in the elastic band group. Knee extension peak torque increased by 16.3% (p < 0.05). TL, EA, TAI, TUG and FTSST decreased by 14.8%, 12.2%, 18.9%, 12.3% and 11.5%, respectively; and MFES increased by 16.2% in the vibration group (p < 0.01). Hip and knee flexion and knee and ankle extension peak torque increased by 19.5%, 18.8%, 30.2% and 30.1% (p < 0.01), respectively, in the elastic band plus vibration group. TAI, TL, EA, TUG and FTSST decreased by 28.5%, 24.6%, 38.3%, 22.4% and 29.0%, respectively, and MFES increased by 42.1% in the elastic band plus vibration group (p < 0.01). The elastic band plus vibration group demonstrated greater improvements in knee and ankle strength compared to single interventions, while the elastic band and vibration groups showed smaller changes (p < 0.05). Additionally TL, EA, TAI, TUG, and FTSST all decreased, while MFES increased (p < 0.05).ConclusionThe combined EBRT and WBVT can enhance knee and ankle isokinetic muscle strength, improve balance ability and physical performance and reduce fear of falls by a greater degree than single interventions. EBRT and WBVT had limited effects on improving lower limb isokinetic muscle strength but enhanced balance ability, physical performance, and reduced fear of falls in older women with a history of falls. Both training modalities showed similar effects.